Human Papilloma Virus16 and 18 Infection and the Cervical Cytology Changes in Combined Hormonal Contraceptive Users: Infeksi Human Papilloma Virus Tipe 16 dan 18 dan Perubahan Sitologi Serviks pada Akseptor Kontrasepsi Hormonal Kombinasi - Merdyana Darkuthni; Mardiah Tahir; Josephine L Tumedia (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To evaluate the correlation between HPV-16 and 18infection and the cervical cytology changes among combinationhormonal contraceptives users. Methods: A cross-sectional study involved 40 women usingcombined hormonal contraceptive (oral or injection/DMPA contraceptive)and 40 women of non-hormonal contraceptive users wasconducted in Dr. Wahidin Sudirohusodo hospital, some affiliatedhospitals of Department of Obstetrics and Gynecology Faculty ofMedicine, Universitas Hasanuddin and a private clinic in Makassarfrom November 2015 and April 2016. HPV 16 and 18 genotypingin cervix using PCR method and cervical cytology changes usingliquid-based cytology (LBC) method were performed. HPV infectionand cervical cytology changes were analysis based on Fisher’s testand chi-square test. Results: A significant difference found only in parity (p<0.05)between users and control of baseline characteristics. Neither usersnor control were significantly associated with HPV-16 and 18infection and changes in cervical cytology. Conclusion: Combined hormonal contraceptives are not correlatedwith HPV-16 and 18 infection and changes in cervical cytology. Keywords: cervix, combined hormonal contraceptive, human papillomavirus